Optimization Of Hydrolysis Of Gayam Peel Waste Using The Acid Method Into Glucose - Sani, Sani; Wirayudha, Umar; Rofiq, Ainur; Suprihatin, Suprihatin (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2025)
This study aims to optimize the hydrolysis process of gayam fruit peel waste using the acid method to produce glucose, which serves as a raw material for bioethanol production. Gayam peel waste contains a high amount of cellulose, which can be converted into glucose through acid hydrolysis. The process began with a delignification step using an 8% NaOH solution at 80°C for 60 minutes to reduce the lignin content. This was followed by hydrolysis using hydrochloric acid (HCl) with varying concentrations (1, 2, 3, 4, and 5 N) and durations (90, 120, 150, 180, and 210 minutes). Optimization was performed using the Response Surface Methodology (RSM) with Minitab 18 software. The RSM results indicated that the highest glucose yield was achieved at a 5 N HCl concentration and 156.67 minutes of hydrolysis time, with a predicted glucose content of 24.37%. Validation using UV-Vis spectrophotometry and the Nelson-Somogyi method showed an actual glucose content of 4.7217% or 47.217 ppm. These findings demonstrate that gayam fruit peel waste can be efficiently converted into reducing sugars and holds significant potential as an environmentally friendly raw material for bioethanol production.